Practice of Alternative Assessment at Tribhuvan University - Neupane, Ram Nath (Tribhuvan Journal, 2023)
Alternative assessment is a recent trend in the field of education. It helps the teachers and students to be more self reflective and responsible towards their tasks and activities. In this light, the present study aimed to explore the practice of alternative assessment system at Tribhuvan University. To accomplish the objective, the researcher adopted interpretivism as philosophical approach and narrative inquiry as research design. This research was based on the experience of university level teachers teaching at semester level. The total population of this study comprised all the teachers teaching at Tribhuvan University. However, the researcher selected only seven English language teachers from Tribhuvan Multiple Campus, Palpa using purposive sampling procedure. Similarly, the researcher made an interview guide, and interviewed with the sampled teachers using recording devices to obtain in-depth information. The results revealed that most of the teachers prefer to use traditional paper pencil test rather than using alternative assessment tools for student evaluation. They had their reluctance to use alternative assessment tools because of the time, resource and investment constraints. They were not properly updated and trained towards alternative assessment. However, they highlighted the importance of such tools for their students’ evaluation. The present study can be useful to the teachers of university level for gaining insights of the alternative assessment tools for student evaluation.